Acoustic cloak constructed with thin-plate metamaterials - Pei Li; Xuebing Chen; Xiaoming Zhou; Gengkai Hu; Ping Xiang (International Journal of Smart and Nano Materials, 2015)
We propose a strategy for designing the cylindrical acoustic cloak with thin-plate metamaterials. The inhomogeneous cloaking shell as derived by transformation acoustics is first discretized into a three-layer anisotropic metafluid, and their material parameters are optimized by minimizing the external scatterings. Then these metafluids are practically realized by thin-plate structures according to the metamaterial concept. As an example, an acoustic cloak is designed with nine layers of thin plate and totally 900 plate units. Numerical simulations are performed to assess the cloaking performance of the designed structure.